State estimation and forecasting using a shadowing filter applied to quincunx and ski-slope models - Auni Aslah Mat Daud (Australia: The University of Western Australia, 2012)
There are an enormous number o f physical phenomenons in this world that appear to behave randomly but are not random: such as the bouncing ball in a pinball machine or a physical device called the Galton board; a rock or any object rolling or sliding down a mountainside or slope.